Seasonal presence of acicular calcium oxalate crystals in the cambial zone of Citharexylum myrianthum (Verbenaceae) - Marcati, Carmen Regina [UNESP]; Angyalossy, Veronica (Brill Academic Publishers, 2005)
This study focuses on the seasonal presence of acicular crystals in the cambial zone of Citharexylum myrianthum Cham. (Verbenaceae). Specimens collected in different months from 1996 to 2000 were examined for the abundance of acicular crystals in the cambium. This information was correlated with the phenology of the species and the climate of the region. Acicular calcium oxalate crystals were found in cambial fusiform and ray cell initials, as well as in their daughter cells. An abundance of crystals was observed during periods of water deficit and leaf fall (July). Fewer crystals were found in the beginning of the wet season and bud swelling (September). When trees were flowering and the soil was wet (November and December), acicular crystals were rarely observed. During this period, acicular crystals were found in differentiating phloem and xylem parenchyma cells, in fully differentiated phloem cells, but not in fully differentiated xylem cells.
Keywords: Acicular crystals; Cambium; Citharexylum myrianthum